Diagnostics of septic myocardial dysfunction in neonates - O.K. Koloskova; N.M. Kretsu (Group of Companies Med Expert, LLC, 2022)
Neonatal sepsis (NS) continues to be the one of the major problems in neonatal practice. This is due to the variability of clinical manifestations and, in part, the lack of available diagnostic markers that are significantly associated with mortality as a result of neonatal sepsis. The purpose - to study the role of paraclinical markers of myocardial dysfunction in neonates with sepsis. Materials and methods. To achieve this goal, 87 newborns (the main group) with manifestations of a generalized infectious-inflammatory process were under our observation. The control group included 30 newborns, in which infectious and inflammatory diseases were refuted. Examination and treatment of patients with NS was carried out in accordance with modern international guidelines and recommendations. Results and discussion. Based on a comprehensive clinical and paraclinical examination of neonates of the main group, it was found that 25 (28.7%) newborns suffered from early sepsis, respectively, the remaining 62 (71.3%) patients had late NS. According to the severity of the condition, 76 (87.4%) children of the main group included in the study required intensive care, which was provided in the neonatal intensive care unit. The average value of procalcitonin in the main observation group was 2.53±0.33 ng/ml, respectively, in the control group - 0.24±0.04 ng/ml (p<0.05). The mean values of creatine phosphokinase, MB fraction and troponin I in the main observation group were 58.44±2.39 U/l and 0.33±0.05 ng/ml, respectively, in the control group - 41.74±2.45 U/l and 0.04±0.01 ng/ml (p<0.05). Conclusions. Generalized infectious-inflammatory process in neonates is accompanied by increased activity of cardiotropic biochemical markers. The study was conducted in accordance with the principles of the Declaration of Helsinki. The research protocol was approved by the Local Ethics Committee of the institution mentioned in the work. Informed consent of the children's parents was obtained for the research. No conflict of interests was declared by the authors.